Improving the yield and nitrogen use efficiency of hybrid rice through rational use of controlled-release nitrogen fertilizer and urea topdressing - Sun, Yuanyuan; Yuan, Xiaojuan; Chen, Kairui; Wang, Haiyue; Luo, Yongheng; Guo, Changchun; Wang, Zhonglin; Shu, Chuanhai; Yang, Yonggang; Weng, Yanfang; Zhou, Xiaobo; Yang, Zhiyuan; et al. (Frontiers in Plant Science, 2023)
Introduction Controlled-release fertilizers effectively improve crop yield and nitrogen use efficiency (NUE). However, their use increases the cost of crop production. Optimal management modes involving urea replacement with controlled-release N fertilizers to increase rice yield through enhanced NUE are not widely explored. Methods Field experiments were conducted from 2017 to 2018 to determine the effects of different controlled-release N fertilizers combined with urea [urea-N (180 kg ha-1, N1)]. We used controlled-release N (150 kg ha-1, N2) as the base, and four controlled-release N and urea-N ratio treatments [(80%:0% (N3), 60%:20% (N4), 40%:40% (N5), or 20%:60% (N6) as the base with 20% urea-N as topdressing at the panicle initiation stage under 150 kg ha-1] to study their impact on the grain yield and NUE of machine-transplanted rice. Results and discussion Grain yield and NUE were positively correlated with increases in photosynthetic production, flag leaf net photosynthetic rate (Pn), root activity, N transport, and grain-filling characteristics. The photosynthetic potential and population growth rate from the jointing to the full-heading stage, highly effective leaf area index (LAI) rate and Pn at the full-heading stage, root activity at 15 d after the full-heading stage, and N transport in the leaves from the full-heading to mature stage were significantly increased by the N4 treatment, thereby increasing both grain yield and NUE. Furthermore, compared with the other N treatments, the N4 treatment promoted the mean filling rate of inferior grains, which is closely related to increased filled grains per spikelet and filled grains rate. These effects ultimately improved the grain yield (5.03-25.75%), N agronomic efficiency (NAE, 3.96-17.58%), and N partial factor productivity (NPP, 3.98-27.13%) under the N4 treatment. Thus, the N4 treatment with controlled-release N (60%) and urea-N (20%) as a base and urea-N (20%) as topdressing at the panicle-initiation stage proved effective in improving the grain yield and NUE of machine-transplanted hybrid indica rice. These findings offer a theoretical and practical basis for enhancing rice grain yield, NUE, and saving the cost of fertilizer.